The Involvement of Glutamate Metabolism in the Resistance to Thermal, Nutritional, and Oxidative Stress in Trypanosoma cruzi. (24th March 2011) - Magdaleno, Anahí; Suárez Mantilla, Brian; Rocha, Sandra C.; Pral, Elizabeth M. F.; Silber, Ariel M.
Abstract : The inhibition of some glutamate metabolic pathways could lead to diminished parasite survival. In this study, the effects of L-methionine sulfoximine (MS), DL-methionine sulfone (MSO), and DL-methionine sulfoxide (MSE), three glutamate analogs, on several biological processes were evaluated. We found that these analogs inhibited the growth of epimastigotes cells and showed a synergistic effect with stress conditions such as temperature, nutritional starvation, and oxidative stress. The specific activity for the reductive amination of α -ketoglutaric acid, catalyzed by the NADP + -linked glutamate dehydrogenase, showed an increase in the NADP + levels, when MS, MSE, and MSO were added. It suggests an eventual conversion of the compounds tested by the T. cruzi cells. The fact that trypomastigote bursting was not significantly inhibited when infected cells were treated with these compounds, remarks the existence of relevant metabolic differences among the different life-cycle stages. It must be considered when proposing a new therapeutic drug.